Edukasi Kesehatan Reproduksi: Pencegahan dan Perawatan Keputihan pada Ibu-Ibu Majelis Taklim Salimah Bali - Suratiah, Suratiah; Runiari, Nengah; Hartati, Nyoman; Surinati, Dewa Ayu Ketut (Jurnal Pengabmas Masyarakat Sehat, 2025)
Leukorrhea (vaginal discharge) is one of the most common gynecological complaints experienced by women of various age groups. While physiological discharge is a normal part of the female reproductive system's defense mechanism, pathological discharge may indicate underlying health issues such as infections caused by bacteria, fungi, or parasites. Lack of knowledge among women, particularly those of reproductive age, often leads to delayed detection and improper treatment. This community service activity aimed to improve knowledge, attitudes, and behaviors related to leukorrhea through direct education. The activity was conducted by the Poltekkes Kemenkes Denpasar team in collaboration with the Salimah Bali Regional Leadership (PW Salimah Bali), using lectures, interactive discussions, distribution of educational leaflets, and pre- and post-tests. The results showed a100% increase in participants' knowledge after the education session, along with positive behavioral changes toward personal hygiene and reproductive health practices. Furthermore, 32 participants expressed willingness to undergo Visual Inspection with Acetic Acid (VIA) screening as a preventive measure against cervical cancer. This program demonstrates that community-based health education is effective in empowering women and promoting early preventive action. Continued collaboration and broader outreach are recommended to sustain and expand the impact of reproductive health education initiatives.